Citrate metabolism in lactic acid bacteria: is there a beneficial effect for Oenococcus oeni in wine? - Eicher, Camille; Coulon, Joana; Favier, Marion; Alexandre, Hervé; Reguant, Cristina; Grandvalet, Cosette (Frontiers in Microbiology, 2024)
Lactic acid bacteria (LAB) are Gram positive bacteria frequently used in the food industry for fermentation, mainly transformation of carbohydrates into lactic acid. In addition, these bacteria also have the capacity to metabolize citrate, an organic acid commonly found in food products. Its fermentation leads to the production of 4-carbon compounds such as diacetyl, resulting in a buttery flavor desired in dairy products. Citrate metabolism is known to have several beneficial effects on LAB physiology. Nevertheless, a controversial effect of citrate has been described on the acid tolerance of the wine bacterium Oenococcus oeni. This observation raises questions about the effect of citrate on the capacity of O. oeni to conduct malolactic fermentation in highly acidic wines. This review aims to summarize the current understanding of citrate metabolism in LAB, with a focus on the wine bacterium O. oeni. Metabolism with the related enzymes is detailed, as are the involved genes organized in cit loci. The known systems of cit locus expression regulation are also described. Finally, the beneficial effects of citrate catabolism on LAB physiology are reported and the negative impact observed in O. oeni is discussed.